Initial Phase 2 Trial of a Nicotinic Agonist in Schizophrenia - Freedman, Robert (2008)
OBJECTIVE: Nicotinic acetylcholine receptors are possible therapeutic targets for schizophrenia, as shown by neurobiological and molecular evidence for deficiencies in expression of α(7)-nicotinic receptors. Patients’ heavy smoking suggests attempted self-medication through this mechanism. The agent 3-(2,4-dimethoxybenzylidene) anabaseine (DMXB-A) is a partial α(7)-nicotinic agonist and can be taken orally. A phase 1 trial showed evidence for cognitive enhancement in schizophrenia. METHOD: Thirty-one subjects with schizophrenia received DMXB-A at two different doses and placebo for periods of 4 weeks in a three-arm, two-site, double-blind, crossover phase 2 trial. The MATRICS Consensus Cognitive Battery assessed cognitive effects, and the Scale for the Assessment of Negative Symptoms (SANS) and Brief Psychiatric Rating Scale (BPRS) assessed clinical effects. Subjects continued their current antipsychotic drug during the trial and were nonsmokers. RESULTS: There were no significant differences in the MATRICS cognitive measures between DMXB-A and placebo over the three treatment arms, but the patients experienced significant improvement at the higher DMXB-A dose on the SANS total score and nearly significant improvement on the BPRS total score. Improvement was most notable on the SANS anhedonia and alogia subscales. Examination of the first treatment arm showed effects of DMXB-A on the attention/vigilance and working memory MATRICS domains, compared to baseline. Five subjects developed mild tremor, and nearly half had mild nausea while taking DMXB-A. CONCLUSION: DMXB-A, a nicotinic agonist that activates α(7)-nicotinic receptors, improved clinical ratings of negative symptoms that are generally resistant to treatment with dopamine antagonist antipsychotic drugs. The clinical utility of this treatment is not yet determined.